Structural investigation on thermoresponsive PVA/poly(methacrylate-co-N- isopropylacrylamide) microgels across the volume phase transition - Ghugare, Shivkumar V.; Chiessi, Ester; Fink, Rainer; Gerelli, Yuri; Scotti, Andrea; Deriu, Antonio; Carrot, Geraldine; Paradossi, Gaio (Macromolecules, 2011)
Characterization of switchable microgels is a major task in drug delivery science. The study of soft polymeric devices requires a combined use of spectroscopy, microscopy, and scattering approaches enabling the characterization of nanostructured features across a volume phase transition. In this work the structural changes of poly(vinyl alcohol) based thermoreversible microgel particles which incorporate p(NiPAAm-co-methacrylate) chains across the transition temperature occurring at 33 °C have been addressed by utilizing reciprocal and direct space approaches such as small angle neutron scattering, SANS, dynamic light scattering, DLS, soft transmittance X-ray microscopy, STXM, and confocal laser scanning microscopy, CLSM, respectively. The comparison between the results obtained from those approaches allows an evaluation of the driving forces acting in the transition and reveals the changes in the microgel structure at nanoscale level. The structure of the poly(vinyl alcohol) based microgel particles, incorporating p(NiPAAm) sequences, consist of a hydrogel core and of a crown of polymer chains projected, at room temperature, in aqueous medium. An increase of the temperature above 33 °C causes a volume phase transition of the system characterized by the collapse of the particle core and of the chains grafted at the particle surface. This transition is accompanied by a massive release of water and an increase of the interface with the dispersing aqueous medium, causing the passage from a permeable to a semipermeable structure. © 2011 American Chemical Society.